From iconic handshapes to grammatical contrasts: Longitudinal evidence from a child homesigner - Coppola, Marie; Brentari, Diane (Frontiers in Psychology, 2014)
Many sign languages display crosslinguistic consistencies in the use of two iconic aspects of handshape, handshape type and finger group complexity. Handshape type is used systematically in form-meaning pairings (morphology): Handling handshapes (Handling-HSs), representing how objects are handled, tend to be used to express events with an agent (“hand-as-hand” iconicity), and Object handshapes (Object-HSs), representing an object's size/shape, are used more often to express events without an agent (“hand-as-object” iconicity). Second, in the distribution of meaningless properties of form (morphophonology), Object-HSs display higher finger group complexity than Handling-HSs. Some adult homesigners, who have not acquired a signed or spoken language and instead use a self-generated gesture system, exhibit these two properties as well. This study illuminates the development over time of both phenomena for one child homesigner, “Julio,” age 7;4 (years; months) to 12;8. We elicited descriptions of events with and without agents to determine whether morphophonology and morphosyntax can develop without linguistic input during childhood, and whether these structures develop together or independently. Within the time period studied: (1) Julio used handshape type differently in his responses to vignettes with and without an agent; however, he did not exhibit the same pattern that was found previously in signers, adult homesigners, or gesturers: while he was highly likely to use a Handling-HS for events with an agent (82%), he was less likely to use an Object-HS for non-agentive events (49%); i.e., his productions were heavily biased toward Handling-HSs; (2) Julio exhibited higher finger group complexity in Object- than in Handling-HSs, as in the sign language and adult homesigner groups previously studied; and (3) these two dimensions of language developed independently, with phonological structure showing a sign language-like pattern at an earlier age than morphosyntactic structure. We conclude that iconicity alone is not sufficient to explain the development of linguistic structure in homesign systems. Linguistic input is not required for some aspects of phonological structure to emerge in childhood, and while linguistic input is not required for morphology either, it takes time to emerge in homesign.